Sound and smoke propagation models for virtual crowd environments - Vaisagh Viswanathan Thattamparambil (2010)
Virtual crowd simulations are important for various applications like defense, social studies, etc. While literature exists on agent design and sensor modeling, there is still no generic model for sound and smoke propagation that can be integrated into existing virtual crowd simulation frameworks. This project attempts to address this issue by creating models for sound and smoke propagation in areas like MRT stations and parade grounds.